Inactivación de pectinmetilesterasa de mango por calentamiento óhmico - Morales Sanchez, E.; Diaz-Cruz, A.; Regalado-Gonzalez, C.; Velazquez de la Cruz, G.; Gonzalez-Jasso, E.; Gaytan-Martinez, M. (Revista Bio Ciencias, 2019)
The work herein is about the thermic inactivation of pectin methylesterase (PME) partially purified mango when applying ohmic heating. The variables of the study were the initial electrical conductivity (0.29 to 0.48 S M-1), the applied electric field (17, 20 and 23 V/cm) and treatment temperature (30 to 72° C). The electrical conductivity was measured in relation to the temperature of Ataulfo mango pulp had 3 ripening levels. It was found that for each ripening level a different electrical conductivity value was obtained, hence, we proceeded to study the effect of the initial electrical conductivity in the inactivation of the PME when ohmic heating is used. It was found that the inactivation of the PME has a direct dependency with the initial electrical conductivity. When the initial electrical conductivity is higher, the inactivation of the PME is also higher at a constant electric field value. On the other hand, it was found that the inactivation of the PME depends on the value of the applied electric field. With a higher applied electric field, the inactivation of the PME is higher. The D values were obtained from the kinetic inactivation of PME when the ohmic heating was applied. It is concluded that the inactivation of mango’s PME by ohmic heating depends on the applied electric field, as it has been widely reported, but it also depends on the initial conductivity.